Believing in Possession: Social Psychological Distress and the Need for Spiritually Oriented Psychological and Pastoral Support - Testoni, Ines (Pastoral psychology, 2025)
This study explores the intersection of beliefs in possession and the need for spiritually oriented psychological support. It addresses the gaps in the current literature regarding the psychological, psychopathological, supernatural, and spiritual dimensions of possession, emphasizing the need for specialized tools among religious and mental health practitioners. The research, conducted with 217 participants in Veneto, Italy, employed both quantitative and qualitative methods to examine the relationship between psychological and spiritual distress. Key findings include a correlation between increased psychological distress and a diminished quality of spiritual life, as well as the impact of perceived meaning in life on coping with spiritual distress. The study highlights the importance of integrating spiritual and existential considerations into mental healthcare to better support individuals experiencing possession-related phenomena. This holistic approach can enhance the understanding and treatment of such conditions, encouraging clinicians to recognize and address the spiritual needs of patients. The research calls for more comprehensive training and awareness among healthcare professionals to adequately address these complex issues.